Profile of the Partner Community of the Service-Learning Program: Maluay, Zamboanguita, Negros Oriental - Oracion, Enrique G. (Silliman Journal, 2022)
This article presents the profile of the partner community of the Silliman University service-learning program. The information for this profile comes from the survey conducted by the faculty coordinator and student-volunteers majoring in Sociology and Anthropology. The data gathered include household demographic profile, socioeconomic characteristics, educational status, health conditions, community and political participation, community problems, and needed intervention programs. The data also include the perception of the community about the capability of Silliman University to work with them and the possible barriers. This information served as the basis for the design of specific projects to be implemented by the participating academic units. At the same time, the gathering of the baseline data was also intended to allow the student to experience the rigors of conducting a sample survey while getting first hand information about lift in a rural community from which they could reflect their own condition. The students found the experience academically as well as socially enhancing.